Investigation of Accident Frequency and Road Condition in Malaysia - Chong, Seng Fah (2015)
This study reviews the relationship of accident frequency and road condition in 36 various selected sites in Peninsula Malaysia. The road accident statistics data were collected from the Jabatan Kerja Raya Malaysia (JKR). The road accident statistics data obtained is from year 2012 to year 2014. Microsoft Excel 2007 was used in this investigation to tabulate the table and plot the graph to show the relationship between road accident frequency and road condition in 36 various selected site in Peninsula Malaysia. This investigation shows that number of accident increase as pavement texture depth and pavement surface friction increases. This investigation also shows that surface friction increase as the pavement texture depth increases. Besides that, this investigation shows that number of accident increase as the speed limit increases.